Application of Zinc Cream as an Adjunct Therapy to Enhance Wound Healing in Diabetic Foot Ulcers - Marito, Lily Putri; Siregar, Rafika Nur; Rostini, Rostini (Jurnal Keperawatan Priority, 2026)
Diabetic foot ulcer is one of the most serious complications in individuals with diabetes mellitus, resulting from peripheral neuropathy, impaired vascularization, and chronic infection, which collectively delay the wound healing process. Proper wound management is essential to prevent severe outcomes such as amputation. Methods: This study employed a case study design to provide an in-depth clinical description of wound healing progression in patients with stage 4 diabetic foot ulcers. Purposive sampling was used to select three patients treated at Asri Wound Care Center Medan. Zinc cream was applied as an adjunct therapy for six weeks, with treatment administered twice weekly. Wound healing was evaluated using the Bates-Jensen Wound Assessment Tool (BWAT) and clinical observations. Results: All patients demonstrated observable improvements in BWAT scores, with reductions from 37 to 22, 40 to 26, and 39 to 24, respectively. Clinical observations indicated improved wound healing indicators, including increased granulation tissue, reduced exudate, and enhanced epithelialization. Conclusion: The application of zinc cream as an adjunct therapy may support the wound healing process in patients with stage 4 diabetic foot ulcers. However, due to the limited sample size and the absence of a control group, the findings should be interpreted cautiously, and further studies with larger samples and comparative designs are recommended.